2011
DOI: 10.1375/ajgc.21.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of a Social Problem-Solving Program on the Aggression of Children

Abstract: The aim of this research was to establish the effect of a social problem-solving training program for 8th grade students. In the experimental group, 14 students were 14 years old and 1 student was 15 years old. In the control group, 13 students were 14 years old and 2 students were 15 years old. The Aggression Questionnaire (AQ) was administered to the students. The students in the experimental group were trained in the Social Problem-Solving program at school. The students in the Social Problem-Solving Traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The findings of the moderated multiple regression analysis in the current study indicating that strong problem solving skills moderates the effect being a victim of bullying has on mental health is consistent with previously discussed research suggesting the importance of problem solving skills in preventing and treating mood disturbance (Kaviani et al, 2011), anger and interpersonal aggression (Secer & Ogelman, 2011), covert bullying and prosocial behaviours (Featherston, 2015), and general wellbeing (O'Neil et al, 2013). In addition, previous research has also found effective problem solving skills to be associated with a reduced impact of negative life events or life circumstance (Grover et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the moderated multiple regression analysis in the current study indicating that strong problem solving skills moderates the effect being a victim of bullying has on mental health is consistent with previously discussed research suggesting the importance of problem solving skills in preventing and treating mood disturbance (Kaviani et al, 2011), anger and interpersonal aggression (Secer & Ogelman, 2011), covert bullying and prosocial behaviours (Featherston, 2015), and general wellbeing (O'Neil et al, 2013). In addition, previous research has also found effective problem solving skills to be associated with a reduced impact of negative life events or life circumstance (Grover et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Problem solving has been widely used in interventions with young people to address a variety of difficulties including anger and interpersonal aggression (Secer & Ogelman, 2011); covert bullying and prosocial behaviours (Featherston, 2015); depression prevention (Poirier, Marcotte, Joly & Fortin, 2013);and general wellbeing (O'Neil, Chalenger, Renzulli, Crasper, & Webster, 2013). Indeed, improving social problem solving skills has been found to improve the social functioning and emotional wellbeing of young people.…”
Section: Interventions Based On Problem Solving Problem Solving Intementioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive behavior is often defined as a self-defeating attempt to solve social problems, which implies that non-adoptive problem-solving might enhance the likelihood of aggression (D'Zurilla et al, 2003). The abilities of SPS are necessary for efficiently dealing with difficulties and might help people to discover effective coping skills instead of behaving aggressively (Seçer & Ogelman, 2011). Gaining the ability of SPS has proven to be helpful in decreasing aggressive behavior through preschool ages and adolescence (Nangle, Erdley, Carpenter, & Newman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…That they feel competent in solving the problem makes positive contribution to their problem-solving skills (Korkut, 2017;Yenice, 2012). Some studies revealed that having problem solving skill has an effect on decrease in aggression, anger, hostility (Seçer & Ogelman, 2011) and in negative behaviors (Bushman & Peacock, 2010), and on increase in social self-efficacy (Erözkan, 2013), positive emotion (D'Zurilla, Maydeu-Olivares, & Pujol, 2011) and interpersonal relationships (Joseph & Strain, 2010;Sumi, 2012). Negative thinking is referred to as negative approach to the problem.…”
Section: Introductionmentioning
confidence: 99%